Digitonthophagus Balthasar, 1959: taxonomy, systematics, and morphological phylogeny of the genus revealing an African species complex (Coleoptera: Scarabaeidae: Scarabaeinae) - Génier, François; Moretto, Philippe (Zootaxa, 2017)
The taxonomy and systematics of the genus Digitonthophagus Balthasar (Coleoptera: Scarabaeidae: Scarabaeinae: Onthophagini) is revised. A detailed study of the male genitalia combined with external morphology suggests that the variability, previously recognized, for D. gazella is hiding a species complex within the Afrotropical region and the Arabian Peninsula. The current study recognizes 16 species; 13 from the Afrotropical region and Arabian Peninsula and three from the eastern portion of the Saharo-Arabian region and the continental Indomalayan region. Species are organized into six species groups based on the results of the morphology-based phylogenetic analysis. The following 12 species are described as new: D. aksumensis Génier new species; D. biflagellatus Génier new species; D. dilatatus Génier new species; D. eucatta Génier new species; D. falciger Génier new species; D. fimator Génier new species; D. namaquensis Génier new species; D. petilus Génier new species; D. sahelicus Moretto new species; D. uks Génier new species; D. ulcerosus Génier new species; and D. viridicollis Génier new species. In order to stabilize nomenclature, lectotypes are designated for Scarabaeus bonasus Fabricius, 1775; Scarabaeus catta Fabricius, 1787, and Onthophagus gazella lusinganus d’Orbigny. A neotype is designated for Scarabaeus dorcas Olivier, 1789 whose status and synonymy need to be altered in order to clarify the status of Scarabaeus gazella auctorum, the widely introduced species with economic importance. A naming scheme is presented for the sclerites of the internal sac. External and male genitalia are illustrated and distribution maps are provided for each species.